2013
DOI: 10.1530/rep-12-0264
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of human cervicovaginal fluid collected before preterm premature rupture of the fetal membranes

Abstract: A significant obstetric complication facing contemporary materno-fetal medicine is preterm premature rupture of the fetal membranes (preterm PROM), which occurs in 30% of all preterm births. The objective of this study was to identify differentially expressed proteins in the cervicovaginal fluid of asymptomatic women before the clinical manifestation of preterm PROM. The preterm PROM group comprised of women with samples collected 6-23 days before PROM, who subsequently delivered preterm (nZ5). Women who spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 56 publications
4
30
0
Order By: Relevance
“…A delicate balance between proteases and antiproteases most likely allows for combating infections, whereas at the same time minimizing tissue damage and inflammation. Studies have indeed shown negative associations between the antiprotease CSTA and known BV complications in pregnant women, [17][18][19] and between the antiproteases CSTA and serine protease inhibitor Kazal-type 5 and HIV acquisition in African sex workers. 15 The authors hypothesized that the latter is likely due to reduced cervicovaginal inflammation, and therefore a reduced influx of CD4 þ CCR5 þ target cells for HIV to mucosal surfaces that are exposed to HIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A delicate balance between proteases and antiproteases most likely allows for combating infections, whereas at the same time minimizing tissue damage and inflammation. Studies have indeed shown negative associations between the antiprotease CSTA and known BV complications in pregnant women, [17][18][19] and between the antiproteases CSTA and serine protease inhibitor Kazal-type 5 and HIV acquisition in African sex workers. 15 The authors hypothesized that the latter is likely due to reduced cervicovaginal inflammation, and therefore a reduced influx of CD4 þ CCR5 þ target cells for HIV to mucosal surfaces that are exposed to HIV.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Furthermore, in vitro studies have shown that lactobacilli do not generally induce human AMPs, whereas BV-associated bacteria (such as Gardnerella vaginalis, A. vaginae and P. bivia) do. 10,12 The cervicovaginal proteome has been characterized by others before, [15][16][17][18][19][20] but never in the context of different VMB compositions. We hypothesized that VMB dysbiosis is associated with cervicovaginal inflammation, and other changes to the mucosal barrier that might cause increased HIV acquisition and other adverse reproductive health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…25 For women who spontaneously labour at a preterm gestation, it is speculated that the Concentration threshold values for albumin (≥19 000 ng/ml) and VDBP (≥90 ng/ml) are based on the results presented in Table 2. *LR+ and OR values were determined using a specificity of >98% as specificities of 100% result in undefined LR+ and OR values.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, we recently found that IL-1ra was significantly decreased by 40% in the CVF of women who subsequently experienced preterm PROM compared with gestation-matched controls. 34 Future studies elucidating the direct role of IL-1ra in fetal membrane physiology could be of interest.…”
Section: Discussionmentioning
confidence: 99%